Human Rights and the Rule of Law: Memories and Reflections - Lester of Herne Hill QC, Lord (Journal of Malaysian and Comparative Law, 2004)
This is a reproduction in its original form (except for slight editorial changes) of the lecture delivered by Lord Lester of Herne Hill QC at the Fourth Tun Mohamad Suffian Public Lecture on 17 December 1996 at the Faculty of Law of the University of Malaya, Kuala Lumpur, Malaysia. Lord Lester of Herne Hill QC is a practising member of the English Bar at Blackstone Chambers and a Liberal Democrat Life Peer.